Evaluation of the structural response under seismic actions using non-linear static methods. - Fragiacomo, M.
The paper investigates the degree of accuracy achievable when some non-linear static procedures based on a pushover analysis are used to evaluate the seismic performance. In order to assess the significance of different sources of errors, three types of structural systems are analysed: (i) single-degree-of-freedom (SDOF) systems with different hysteretic behaviour; (ii) shear-type multi-degree-of-freedom (MDOF) systems with elastic?perfect plastic (EPP) shear force?interstorey drift relationships; (iii) a steel moment-resisting frame with rigid joints and EPP moment?curvature relationship. In SDOF systems, the source of approximation comes only from the calibration of the demand spectrum, while in MDOF systems some further errors are introduced by the schematization with an equivalent SDOF system. The non-linear static procedures are compared with rigorous time-history analyses carried out by considering ten generated earthquake ground motions compatible with the Eurocode 8 elastic spectra. It was found that SDOF systems with longer periods satisfy the equal displacement approximation regardless of the hysteretic model, while hysteresis loops with smaller energy dissipated indicate lower response for shorter periods. This is the opposite of what predicted by the ATC-40 capacity spectrum method, which underestimates and overestimates, respectively, the actual response of low- and high-ductility systems. Conversely, the inelastic spectrum method proposed by Vidic, Fajfar and Fischinger leads to the most accurate results for all types of structural systems. The analyses carried out on EPP shear-type frames point out a large concentration of the ductility demand on some storeys. However, such a concentration markedly reduces when some hardening is accounted for.
Keywords: Inelastic spectra; Performance-based design; Pushover analysis; SDOF systems; Seismic analysis; Shear-type frames